Breast cancer incidence: Decreasing trend in large tumours in women aged 50–74. (December 2017) - Molinié, Florence; Delacour-Billon, Solenne; Tretarre, Brigitte; Delafosse, Patricia; Seradour, Brigitte; Colonna, Marc
Objective: A decrease in advanced breast cancer incidence is considered an early indicator of breast cancer mortality reduction in a screening programme. We describe trends in breast cancer incidence according to tumour size and age in three French administrative areas, where an organized screening programme was implemented during the 1990s. Methods: Our study included all 28, 092 invasive breast cancers diagnosed from 2000 to 2010 in women living in three areas (Hérault, Isère, Loire-Atlantique). Age, year of diagnosis, and size of tumour at diagnosis was provided by the three area cancer registries. Poisson regression models were fitted to estimate changes in incidence over time, after adjustment for age and administrative area. Results: From 2000 to 2010, the incidence rate of large (tumour size >20 mm) breast cancer linearly decreased in women aged 50–74 (target age of the screening programme) from 108.4 to 84.1/100, 000 (annual percent change = −1.9%, p  < 0.001). No change in large breast cancer incidence rate was found in women aged 20–49, or older than 74. Conclusions: A decreasing trend in incidence of large tumour size breast cancer in the target age of the screening programme is demonstrated for the first time in France. The overall 20.9% linear decrease over 11 years in these three areas is encouraging and should be closely monitored and extended to other areas of France, where the screening programme was generally implemented only in 2004.